Application of tribo-electrostatic separation (T-ES) technique for fractionation of plant-based food ingredients. (May 2022) - Yang, Jingsi; Meda, Venkatesh; Zhang, Lifeng; Nickerson, Michael
Abstract: The worldwide pressure on food consumption has evoked the urgent need of sustainable sources of nutrients, especially with a dramatic increase in population in recent decades. To keep pace with the increasing demand for health beneficial foods, a tribo-electrostatic separation (T-ES) technique, the development of which has been accelerated in the past two decades, has attracted more and more attention as a fractionation method due to its high efficiency, low cost, environmental-friendly characteristics and potential of generating new and higher value plant-based products. Charging particles by physical contact against each other and/or friction between particles and the contact material followed by the separation in an electric field, the T-ES technique has been developed and applied in fractionation of protein and starch in different pulses and cereals. Equipment of different designs have been developed and proven to be effective in separating these food ingredients. Although it is a promising technology, the obscure understanding of the charging mechanism between the tribo-charger and the agro-materials, and some "seemingly-conflicting" conclusions among published papers have indicated the challenges and gaps of this technique, which highlights the necessity of continuous efforts before comprehensive insights can be obtained. This review aims at providing a comprehensive landscape of the application of the tribo-electrostatic technique in the different kinds of crops, in particular on the technical design and influencing factors, to date. Highlights: A tribo-electrostatic separation technique to separate agro-particles was focused. The tribo-charging sensitivity and the uniqueness of food powders were highlighted. Conflicting conclusions among published papers have been observed and presented. Scientific challenges for utilization of TEST in food materials were overviewed. Typical TEST designs were summarized with potential paths for future study proposed.